Perceptions of Students Learning French as a Foreign Language in Malaysia - POINT, RODOLPHE GILLES; NG, CHIA-CHUN; TING, SU HIE (Trends in Undergraduate Research, 2021)
The study investigated the perceptions of students learning French as a foreign language in a Malaysian public university. The specific objectives were to examine: (1) the self-reported French language proficiency level; and (2) their perceptions of their listening, speaking, reading and writing skills in French. Questionnaire data were collected from 80 undergraduates enrolled in French Levels 1 and 2 courses. The analysis showed that language learners from Level 1 and Level 2 rated themselves as having fair proficiency level when they made their rating without comparing themselves to a French native speaker. However, when they compared themselves with a native French speaker, more of them rated their proficiency as poor. The results showed that the relative difficulty of mastering language skills in French, from the most difficult to the easiest, are writing, speaking, reading and listening. Similar results were found for Level 1 and Level 2 French but the undergraduates struggled with writing and speaking at Level 2 more than at Level 1 because of an increased vocabulary range, greater grammatical complexity and longer texts. The results suggest that the difficulties are not much in comprehension of the language but more towards expressing themselves whether in speaking or writing.